Actividades para la enseñanza de la topología a estudiantes de educación básica primaria, secundaria y superior (2017)
In the field of Mathematics, it is very important to maximize geometric and metric thinking in the different schooling levels. Nonetheless, we currently notice that basic notions of topology that are essential for the development of mathematical thinking, as proposed by Piaget and Inhelder (1975), who emphasize the importance of boarding these notions for the development of spatial structures, are not taken into account. However, when reviewing the mathematics standards (2006) of the National Ministry of Education (MEN, for its acronym in Spanish), notions of graph theory are only presented until the eight grade; without this being proof of the execution in the schools’ curriculums.